104 Prognostic utility of calculated plasma volume status in chronic heart failure. (9th June 2011) - Ling, H Z; Aung, N; Flint, J; Aggarwal, S; Weissert, S; Cheng, A; Francis, D P; Mayet, J; Thomas, M; Woldman, S; Okonko, D O
Abstract : Background: Plasma volume (PV) expansion is a hallmark feature of worsening heart failure that is notoriously underestimated by clinical examination. While radioisotope assays optimally quantify PV status, numerous haemodialysis-based equations also exist for its estimation. The prognostic utility of such formulas in chronic heart failure (CHF) is unknown. Methods: We analysed the relation between estimated PV status and mortality in 246 outpatients with CHF (mean (±SD) age 67±13 years, NYHA class 2±1, LVEF 28±8%). PV status was calculated (Hakim RM, et al) by subtracting the patients actual PV ((1-haematocrit) × (a + (b × weight)); a and b are gender-specific constants) from their ideal PV ((c × weight); c=gender-specific constant). Results: Median (±IQR) PV status was—261±550 ml with 78% and 21% of patients having PV contraction and expansion, respectively. Patients with PV excess had significantly higher creatinine and lower albumin levels. Over a median follow-up of 13±16 months, 36 (15%) patients died. PV status predicted mortality (HR 1.001, 95% CI 1.001 to 1.002, p=0.001) in a graded fashion (Abstract 104 figure 1A ) and did so independently of NYHA class, LVEF, weight, haematocrit and creatinine. A PV status ≤−178 ml optimally predicted survival (ROC AUC 0.68, p=0.0007) and conferred a 75% reduced hazard for death (HR 0.16, 95% CI 0.07 to 0.37, p<0.0001, Abstract 104 figure 1B ). Conclusions: Calculating plasma volume status in CHF patients appears prognostically useful and suggests that dehydration is better tolerated than volume excess in these individuals and that targeting therapy to achieve a plasma volume status ≤178 ml might increment survival.